Pemberdayaan Diaspora Indonesia di Malaysia melalui Pelatihan Honey Soap Crafting sebagai Peningkatan Life Skill - Evi Susanti; Claresia Tsany Kusmayadi; Habiddin Habiddin; Sentot Kusairi; Sri Rahayu Lestari (Indonesian Journal for Social Responsibility, 2026)
The training on making solid honey soap in an artisanal style was conducted as a form of life skill enhancement for the Indonesian diaspora in Malaysia, particularly those working in the informal sector. The partner group in this activity was students of the Klang Lama Assisted Learning Center, which is part of the Indonesian diaspora community. The training program was designed to improve participants’ competencies in creative honey soap production. The activities were carried out in three stages: the first stage involved preparation, including the signing of a memorandum of understanding (MoU) with partners, identification of participants’ needs, development of a pocket handbook, and provision of materials; the second stage consisted of implementation through material delivery and independent hands-on practice; and the final stage involved evaluation using pretest and posttest to measure improvements in participants’ skills and life skills. The evaluation results showed that 100% of the students stated that the training was beneficial, easy to understand, and provided new skills in handicraft production, particularly honey soap. Furthermore, 68.75% of the students expressed interest in making soap independently after the training. This program was proven to be effective in enhancing practical skills and life skills within the Indonesian diaspora community.